Analysis of hip joint loading during walking with different shoe types using instrumented total hip prostheses - Palmowski, Y. (Sci Rep, 2021)
Hip joint loads need careful consideration during postoperative physiotherapy after joint replacement. One factor influencing joint loads is the choice of footwear, but it remains unclear which footwear is favorable. The objective of the present study was to investigate the influence of footwear on hip joint loads in vivo. Instrumented hip endoprostheses were used for in vivo load measurements. The parameters resultant contact force (F(res)), bending moment (M(bend)) and torsional moment (M(tors)) were evaluated during treadmill walking at 4 km/h with different shoe types. In general, footwear tended to increase hip joint loading, with the barefoot shoe having the least influence. F(res) and M(bend) were significantly increased during heel strike for all shoe types in comparison to barefoot walking, with everyday shoe (34.6%; p = 0.028 and 47%; p = 0.028, respectively) and men’s shoe (33.2%; p = 0.043 and 41.1%; p = 0.043, respectively) resulting in the highest changes. M(tors) at AbsMax was increased by all shoes except for the barefoot shoe, with the highest changes for men’s shoe (+ 17.6%, p = 0.043) and the shoe with stiffened sole (+ 17.5%, p = 0.08). Shoes, especially those with stiff soles or elaborate cuishing and guiding elements, increase hip joint loads during walking. The influence on peak loads is higher for M(tors) than for F(res) and M(bend). For patients in which a reduction of hip joints loads is desired, e.g. during physiotherapy after recent surgery or to alleviate symptoms of osteoarthritis, low profile shoes with a flexible sole may be preferred over shoes with a stiff sole or elaborate cushioning elements.